Recent Advances in Radical Addition to Alkenylboron Compounds. Issue 16 (11th December 2019) - Lovinger, Gabriel J.; Morken, James P.
Abstract : The addition of carbon‐centered radicals to alkenylboron compounds provides a useful method for the construction of organoboron reagents which are versatile reagents in chemical synthesis. While the first examples of this type or process appeared 70 years ago, until recently, attention to this type of reaction has been limited. A number of examples of this reactivity have been demonstrated recently, and strategies are emerging that allow for tuning the reagent structure in order to modulate reactivity. This review surveys recent advances in this class of reaction. Abstract : Organoboron compounds are important reagents in chemical synthesis. While a plethora of catalytic and non‐catalytic two‐electron processes have been used to construct these motifs, recent studies have begun to broaden the scope of radical‐based synthesis strategies that apply to these targets. This minireview highlights the construction of organoboron compounds by addition to alkenyl boron reagents.